2020
DOI: 10.1111/anu.13189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental dietaryHaematococcus pluvialison growth performance, antioxidant capacity, immune responses and resistance toVibrio harveyichallenge of spotted sea bassLateolabrax maculatus

Abstract: The present study was conducted to investigate the effects of Haematococcus pluvialis on growth performance, antioxidant capacity, immune responses and resistance to Vibrio harveyi of spotted sea bass Lateolabrax maculatus. Fish were fed with six diets containing grade levels of containing H. pluvialis (0, 2, 4, 6, 8 and 1 g/kg, respectively) in triplicate for 8 weeks, followed by a V. harveyi infection test for 7 days. The astaxanthin concentrations of diets were 1.14 (control), 30.23 (T1), 58.42 (T2), 91.51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…H. pluvialis could accumulate high levels of astaxanthin (3-5% dry weight) (Lorenz and Cysewski, 2000;Ambati et al, 2014) and is regarded as the most potent natural source of astaxanthin (Bowen et al, 2002). Several studies indicated that dietary supplementation of H. pluvialis would improve the color, immune and antioxidant capacity of fish (Moretti et al, 2006;Sheikhzadeh et al, 2012;Li et al, 2018;Yu et al, 2021). However, H. pluvialis red cysts typically have thick and less digestible cell walls (Hagen et al, 2002;Shah et al, 2016), which reduce the bioavailability of astaxanthin (Sommer et al, 1991;Choubert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…H. pluvialis could accumulate high levels of astaxanthin (3-5% dry weight) (Lorenz and Cysewski, 2000;Ambati et al, 2014) and is regarded as the most potent natural source of astaxanthin (Bowen et al, 2002). Several studies indicated that dietary supplementation of H. pluvialis would improve the color, immune and antioxidant capacity of fish (Moretti et al, 2006;Sheikhzadeh et al, 2012;Li et al, 2018;Yu et al, 2021). However, H. pluvialis red cysts typically have thick and less digestible cell walls (Hagen et al, 2002;Shah et al, 2016), which reduce the bioavailability of astaxanthin (Sommer et al, 1991;Choubert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%